Estimating the efficiency from Brazilian banks: a bootstrapped Data Envelopment Analysis (DEA) - Ana Elisa Périco; Naja Brandão Santana; Daisy Aparecida do Nascimento Rebelatto (Production)
Abstract The Brazilian banking sector went through several changes in its structure over the past few years. Such changes are related to fusions and acquisitions, as well as the largest market opening to foreign banks. The objective of this paper is to analyze, by applying the bootstrap DEA, the efficiency of banks in Brazil in 2010-2013. The methodology was applied to 30 largest banking organizations in a financial intermediation approach. In that model, the resources entering a bank in the form of deposits and total assets are classified as inputs and besides these manual labor is also considered as a resource capable of generating results. For the output variable, credit operations represent the most appropriate alternative, considering the role of the bank as a financial intermediary. In this work, the matter of the best classification among retail banks and banks specialized in credit has little relevance. The low relevance in this type of comparison is a result of analysis by segments (segments were analyzed separately). The results presented here point to an average level of efficiency for the large Brazilian banks in the period. This scenario requires efforts to reduce expenses but also to increase revenues.